PENGARUH CAPITAL ADEQUANCY RATIO, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL, DAN NON PERFORMING LOAN TERHADAP RETURN ON ASSETS (Survei pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Tahun 2016 – 2018) - Dwi Puji Lestari; Edi Wibowo; Setyaningsih Sri Utami (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This research was used to analyze the effect of Capital Adequacy Ratio, Operational Cost of Operating Income and Non Performing Loans on Return On Assets on Commercial Banks listed on the Indonesia Stock Exchange in 2016 – 2018. The overall population in this study was 43 public banks. The research sample consisted of 10 commercial banks with the sampling technique was purposive sampling. The results of this study indicate that partially Operating Costs Operating Income and Non Performing Loans have a significant effect on Return On Assets while Capital Adequancy Ratio has no significant effect on Return On Assets. Simultaneously Capital Adequancy Ratio, Operational Costs Operating Income and Non Performing Loans have a significant effect on Return On Assets.